Efforts to Improve Letter Recognition Skills Using Flashcards among Students at the Muhammadiyah Guidance Center, Kepong, Malaysia - Marbun, Jesica Br; Nasution, Dewi Kesuma (Universitas Pahlawan Tuanku Tambusai, 2025)
Education plays an important role in improving the quality of human resources, including reading skills acquisition. However, preliminary observations indicate that students' reading skills at Sanggar Bimbingan Muhammadiyah Kepong, Malaysia, are still low. This study aims to improve students' reading skills through the use of Flash Card media. The research method used is Classroom Action Research (CAR), conducted in two cycles, where each cycle includes planning, implementation, observation, and reflection. Data was collected through observations, reading skills tests, and documentation. The results of the study show that the use of Flash Card media significantly improves students' reading skills. In the pre-action stage, the average student score was only 43, with a mastery percentage of 47.37%, categorized as low. After implementing Flash Card media in Cycle I, the average score increased to 57, with a mastery percentage of 57% (categorized as moderate). In Cycle II, there was a significant improvement, with an average score of 91.42 and a mastery percentage of 88.2% (categorized as very good). Additionally, students' confidence in reading improved, as well as their active participation in learning. The conclusion of this study is that Flash Card media is effective in enhancing students' reading skills. The combination of Flash Cards with interactive learning methods has been proven to enhance students' understanding, reading speed, and memory retention of letters and words. Therefore, Flash Card media is recommended as an innovative learning strategy to improve students' reading skills.